2017
DOI: 10.2147/nss.s123319
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone viewing distance and sleep: an experimental study utilizing motion capture technology

Abstract: There are studies reporting the negative impact of smartphone utilization on sleep. It is considered that reduction of melatonin secretion under the blue light exposure from smart-phone displays is one of the causes. The viewing distance may cause sleep disturbance, because the viewing distance determines the screen illuminance and/or asthenopia. However, to date, there has been no study closely investigating the impact of viewing distance on sleep; therefore, we sought to determine the relationship between sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 27 publications
2
33
0
2
Order By: Relevance
“…In addition, based on recent studies on melatonin, the blue light emitted from a display such as a smartphone may play some role in sleep disturbance by altering melatonin . Moreover, we found that smartphones, when used in bed, are placed closer to subjects’ faces compared to other times of use, so any effects caused by the blue light may be stronger in that position …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In addition, based on recent studies on melatonin, the blue light emitted from a display such as a smartphone may play some role in sleep disturbance by altering melatonin . Moreover, we found that smartphones, when used in bed, are placed closer to subjects’ faces compared to other times of use, so any effects caused by the blue light may be stronger in that position …”
Section: Discussionmentioning
confidence: 74%
“…62 Moreover, we found that smartphones, when used in bed, are placed closer to subjects' faces compared to other times of use, so any effects caused by the blue light may be stronger in that position. 63 Furthermore, in research that examined Internet dependence over different years in the same region and with the same age group, the prevalence of PIU was found to be higher in newer surveys. 64 Increased accessibility to the Internet and commercial development of attractive devices and applications will likely continue to increase PIU scores in the future.…”
Section: Discussionmentioning
confidence: 97%
“…Yoshimura et al recently found that the viewing distance in the lying position was shorter than that in the sitting position, considering smartphones distances correlated negatively with subjective sleep status [16]. An American pilot study compared asthenopia using e-readers VS traditional paper format, constating a significantly higher rate of eyestrain (p = 0.008) and irritation (p = 0.011) in electronic devices group [17].…”
Section: Discussionmentioning
confidence: 99%
“…We therefore need to investigate and accumulate our knowledge to control the negative biological effects of blue light. Previous studies have suggested the influences of the distance to light source emitting blue light [14] and the angle of incidence on the eye. Studies reported that white light exposure to the inferior retina causes greater melatonin suppression than exposure to the superior retina [15,16].…”
Section: Introductionmentioning
confidence: 99%